The Impact of COVID-19 Pandemic on Customer Satisfaction and Business Performance - Tek Yew Lew; Lim Hui Ling; Ahmad Azeedi Reza Bin Mohd Fuad; Afra Binti Akbal Khan; Aimi Aleeya Binti Ismail; Ainun Adibah Binti Mohammad Hazaini; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, triggered significant global disruptions, leading to widespread restrictions aimed at controlling the virus's spread. These restrictions prompted businesses to rapidly adapt, with a strong focus on digitalization, to meet evolving consumer demands. This study examined the impact of the COVID-19 pandemic on customer satisfaction and business performance in Malaysia. Data were collected from 150 customers and business owners through surveys and observational methods. The findings revealed that perceived usefulness and business reaction were highly significant factors influencing customer satisfaction and business performance. Additionally, perceived overall performance played a crucial role in how businesses navigated the pandemic. However, perceived satisfaction was not a significant predictor, suggesting that while businesses successfully adapted, these changes did not necessarily lead to higher customer satisfaction. The study underscores the importance of agile and customer-centric strategies, emphasizing that businesses must continue to evolve their operational approaches to survive and thrive in an increasingly uncertain environment.